Edukasi Financial Capability: Mempersiapkan Generasi Muda Mencapai Financial Well-Being - Yanuar Bachtiar; Tri Ramaraya Koroy; Masithah Akbar; Rizky Nastiti; Normalina; Saifhul Anuar Syahdan; Norbaiti; R.R Siti Munawaroh; Iqbal Firdaus (Abdimas Universal, 2022)
In line with the growing trend of online shopping with all the conveniences offered, the ability to manage finances also needs to be improved so that excessive consumptive behavior does not occur. In addition, the importance of understanding about financial capability is very important for the younger generation, especially students who will later face the world of work which requires them to be able to manage their finances independently and efficiently. Therefore, this educational activity is intended to provide insight for students in planning their financial management. This activity is attended by 80 online participants. This activity does not only focus on the provision of materials but also the practice of financial management. Based on the results of the pre-test, it was found that most of the participants still did not understand the importance of being able to manage their finances. Then, from the post-test results, it was found that after participating in this activity, the participants were able to understand more about financial management. By attending this activity, it is hoped that participants will have a better understanding of financial capability and be able to apply the knowledge they have gained in managing their finances in their daily lives.